Bacteria-derived fluorescent carbon dots for highly selective detection of p-nitrophenol and bioimaging. Issue 18 (6th August 2019) - Zhang, Shengting; Zhang, Dongfang; Ding, Yafang; Hua, Jianhao; Tang, Bing; Ji, Xiuling; Zhang, Qi; Wei, Yunlin; Qin, Kunhao; Li, Bo
Abstract : Schematic of the synthetic route for fluorescent CDs-BC and their applications in the detection of p -NP and bioimaging. Abstract : p -Nitrophenol ( p -NP) pollutants are widely present in soil and aquatic environments and can seriously impair the health of living beings. Hence, a rapid, sensitive, and selective method for p -NP detection is urgently needed. Herein, for the first time, we successfully synthesized fluorescent carbon dots (CDs) from Bacillus cereus (BC) via a one-step hydrothermal process. The obtained CDs-BC can be applied as a rapid, highly selective, and sensitive sensor for p -NP detection. The fluorescence quenching efficiency of the CD-BC sensor exhibited excellent linear responses with p -NP concentrations at both 0.3–6.5 μM and 6.5–30 μM, with a detection limit of 0.11 μM. The mechanism of p -NP detection is based on the inner filter effect (IFE). Preliminary bacteria, cell, and animal studies showed that the as-prepared CDs-BC possess high photostability, excellent biocompatibility, low or no biotoxicity, and multicolor fluorescence emission properties; furthermore, they can be rapidly excreted from the body of mice, which suggests their potential for applications in the biomedical field.